Water resources of Cyprus under changing climatic conditions: Modelling approach, validation and limitations - Cleridou, Niki; Benas, Nikolaos; Matsoukas, Christos; Croke, Barry; Vardavas, Ilias Mihail (My University, 2014)
We examine trends in the water resources of Cyprus by focussing on water flux changes in the important Kouris catchment. Our modelling approach is general and is a synthesis of an adapted conceptual daily rainfall-runoff model, radiation transfer models that use high resolution MODIS satellite climatological data and GCM scenarios for future climatic change. We used climatic data as input to our models, downscaled to the catchment resolution from two climate scenarios: the mild RCP2.6 and the extreme RCP8.5, to estimate water resources by the end of the 21st century. The models show that the present mean annual rainfall resource of 174Mm3 will be reduced to 162Mm3 and 132Mm3, for the mild and extreme scenario, respectively. The present mean discharge of 21.5Mm3 into the Kouris dam from the catchment will decrease to 16.6Mm3 and 6.9Mm3 under the mild and extreme scenario, respectively.
Keywords: Catchment; Climate change; Potential evaporation; Rainfall-runoff; Water resources